Intra-Abdominal Hemorrhagic Catastrophe due to Large Subserous Myomatous Capsular Venous Rupture - Tamilselvi Sethupathy; Madhankumar Madathupalayam; Krithika Arun Prasad (Case Reports in Obstetrics and Gynecology)
Uterine leiomyoma is a common benign uterine tumor of women in the reproductive age group. Although the common symptoms of leiomyoma are menorrhagia and dysmenorrhoea, this patient presenting as a near collapse is a rare finding. The patient presented with abdominal pain and worsening anemia within a span of hours and hypotension, tachycardia, and tachypnoea needing urgent surgical intervention and blood transfusion and intensive care support is relatively rare. Though every effort to know the exact cause of intraperitoneal hemorrhage in this patient was taken, the rarer diagnosis of capsular venous rupture was not identified prior to surgical intervention. Initially, laparoscopy was introduced first to identify the cause of massive hemorrhage; the approach was changed to open myomectomy keeping in mind the general condition of the patient. Hence, for any patient with a prior diagnosis of myoma with hemodynamic instability, the rarer diagnosis of leiomyomatous capsular venous erosion should be a differential diagnosis to aid in the appropriate management of the women. The team of interdisciplinary expertise will definitely improve the outcomes in such cases.